1998
DOI: 10.1152/ajpheart.1998.275.2.h668
|View full text |Cite
|
Sign up to set email alerts
|

Estimating glucose metabolism using glucose analogs and two tracer kinetic models in isolated rabbit heart

Abstract: The purpose of this investigation was to 1) evaluate the relative accuracy of the Sokoloff and Patlak tracer kinetic models in estimating glucose metabolic rate (GMR) in the presence and absence of insulin; 2) evaluate the effect of nutritional state on the lumped constant (LC); and 3) compare the kinetics of 2-fluoro-2-deoxy-d-[14C]glucose (FDG) and 2-deoxy-d-[3H]glucose (DG) membrane transport and phosphorylation. The experimental preparation was the isolated, red blood cell-albumin-perfused rabbit heart. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Indeed, some studies conducted on rabbits 30 and rats [31][32][33] have shown a difference between the uptake of 18 FDG and the glucose molecule, with variations in insulin concentration 29 , the presence of competitive substrates 29 , and the ischaemia-reperfusion sequence [32][33][34] . These differences of uptake between the tracer and the substrate molecule would be due to the variations of the lumped constant that would not always be equal to 0.67 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies conducted on rabbits 30 and rats [31][32][33] have shown a difference between the uptake of 18 FDG and the glucose molecule, with variations in insulin concentration 29 , the presence of competitive substrates 29 , and the ischaemia-reperfusion sequence [32][33][34] . These differences of uptake between the tracer and the substrate molecule would be due to the variations of the lumped constant that would not always be equal to 0.67 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of compartmental models to describe [ 18 F]FDG kinetics in human skeletal muscle has recently seen important contributions (14,15,19,26,34). Common to all these reports is the tacit assumption that the 3K and 4K models, which were originally proposed to describe [ 18 F]FDG kinetics in the brain (24,31), also provide the appropriate compartmental structure for studying human skeletal muscle.…”
Section: Model Structurementioning
confidence: 99%
“…Recent reports indicate that the lumped constant is relatively insensitive to insulin (16,23,33), but glucose and [ 18 F]FDG individual unit processes exhibit different affinity. However, [ 18 F]FDG has proven to be a sensitive probe for assessing the individual steps of metabolism in human skeletal muscle in various physiopathological states (14,15,19,26,30,34).…”
mentioning
confidence: 99%
“…In myocardial tissue, the dephosphorylation rate is negligible [26], and thus the accumulation of glucose analogues in the myocyte can essentially be viewed as a combination of transport and phosphorylation. The rate of transport is governed by the number of transporters present at the sarcolemma and the affinity of the transporters for their respective substrates.…”
Section: Discussionmentioning
confidence: 99%